ASSESSING THE STABILITY OF ESCIN - Jamshidovna , Yokubova Nilufar (Journal of Higher Education and Academic Advancement, 2024)
Drug quality and stability are intricately linked, with temperature, light, and humidity playing crucial roles in their preservation. It is imperative for pharmacy experts to ascertain the shelf life of drugs by studying various factors such as extraction, storage, transportation, and more to establish ideal storage conditions and expiration dates. While standard stability tests are conducted based on industry guidelines, conducting accelerated tests for certain temperature-sensitive drugs, particularly herbal medicines, presents challenges. As a result, natural (continuous) tests are relied upon as the primary method for determining stability. Based on these considerations, the shelf life of Escin was determined solely through natural testing